2016
DOI: 10.1371/journal.pone.0167316
|View full text |Cite|
|
Sign up to set email alerts
|

New Insights on the Composition and the Structure of the Acellular Extrinsic Fiber Cementum by Raman Analysis

Abstract: Acellular extrinsic fiber cementum is a mineralized tissue that covers the cervical half of the tooth root surface. It contains mainly extrinsic or Sharpey’s fibers that run perpendicular to the root surface to anchor the tooth via the periodontal ligament. Acellular cementum is continuously and slowly produced throughout life and exhibits an alternating bright and dark pattern under light microscopy. However, although a better understanding of the structural background of acellular cementum is relevant to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 45 publications
0
26
0
1
Order By: Relevance
“…Alternating light and dark bands, about 2.5 !m thick [12] seen in undemineralised ground sections of teeth in transmitted light microscopy (TLM) correspond with alternating levels of mineralisation. Dark bands are thought to correspond with slower forming cementum, and light bands with faster forming cementum but which bands are more or less mineralised remains unclear [15,[18][19][20]. Using Raman polarised acquisitions, Colard et al [18] have also observed better aligned collagen fibres within dark bands than in light bands, with mineral crystals always lying parallel to the collagen fibres.…”
Section: Incremental Markings In Cementummentioning
confidence: 99%
See 1 more Smart Citation
“…Alternating light and dark bands, about 2.5 !m thick [12] seen in undemineralised ground sections of teeth in transmitted light microscopy (TLM) correspond with alternating levels of mineralisation. Dark bands are thought to correspond with slower forming cementum, and light bands with faster forming cementum but which bands are more or less mineralised remains unclear [15,[18][19][20]. Using Raman polarised acquisitions, Colard et al [18] have also observed better aligned collagen fibres within dark bands than in light bands, with mineral crystals always lying parallel to the collagen fibres.…”
Section: Incremental Markings In Cementummentioning
confidence: 99%
“…Dark bands are thought to correspond with slower forming cementum, and light bands with faster forming cementum but which bands are more or less mineralised remains unclear [15,[18][19][20]. Using Raman polarised acquisitions, Colard et al [18] have also observed better aligned collagen fibres within dark bands than in light bands, with mineral crystals always lying parallel to the collagen fibres. Lieberman [15] suggested nutritional status determines the rate of acellular cementum formation but also that changes to the magnitude and frequency of chewing forces underlie shifts in the orientation of the principal collagen fibres within the PDL that in turn determine the angle at which Sharpey's fibres become embedded within forming cementum [21].…”
Section: Incremental Markings In Cementummentioning
confidence: 99%
“…A recent in situ second‐harmonic‐generation study has also shown that collagen fibers produced by preosteoblast MC3T3‐E1 cell cultures are in general less structured and nonspecifically orientated due to immature structure . In addition, the collagen amide III band at ~1,270 cm −1 is known to be strongly polarization‐dependent compared with the ~1,240 cm −1 band and therefore would be more sensitive to the orientation of collagen fibrils, especially in native bone. It has recently been shown that the orientation and alignment of cells in osteogenic culture can be increased by using artificially orientated collagen scaffolds or by mechanical stimulation .…”
Section: Resultsmentioning
confidence: 99%
“…Lipid/matrix ratios were not calculated because of the possible dissolution of lipids by ethanol during the fixation step . In addition, given that all spectra were acquired using a high‐NA objective, we advise that the intensity of the amide III subband at ~1,270 cm −1 used to calculate the 1,240/1,270 cm −1 ratios may also exhibit some polarization dependence …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a study undertaken by Cool and colleagues [7] reported that cementum growth layers are not the result of changes in mineral density at all, as they failed to detect cementum growth layers using scanning electron microscope (SEM) equipped with backscattered electrons detector (BSE). The most recent study on composition and structure of AEFC, using Raman imaging analysis [8] argues that darker AEFC lines correspond to higher mineral/organic ratio when compared to brighter lines.…”
Section: Introductionmentioning
confidence: 99%